Harnessing Digital Health Technologies During and After the COVID-19 Pandemic: Context Matters - Petracca, Francesco; Ciani, Oriana; Cucciniello, Maria; Tarricone, Rosanna (Journal of Medical Internet Research, 2020)
A common development observed during the COVID-19 pandemic is the renewed reliance on digital health technologies. Prior to the pandemic, the uptake of digital health technologies to directly strengthen public health systems had been unsatisfactory; however, a relentless acceleration took place within health care systems during the COVID-19 pandemic. Therefore, digital health technologies could not be prescinded from the organizational and institutional merits of the systems in which they were introduced. The Italian National Health Service is strongly decentralized, with the national government exercising general stewardship and regions responsible for the delivery of health care services. Together with the substantial lack of digital efforts previously, these institutional characteristics resulted in delays in the uptake of appropriate solutions, territorial differences, and issues in engaging the appropriate health care professionals during the pandemic. An in-depth analysis of the organizational context is instrumental in fully interpreting the contribution of digital health during the pandemic and providing the foundation for the digital reconstruction of what is to come after.